Monitoring of the anticoagulants argatroban and lepirudin: a comparison of laboratory methods - Ivandic, Boris; Zorn, Markus (Clinical and applied thrombosis, hemostasis, 2011)
Monitoring of direct inhibitors of thrombin (DTI) is critical for their safe and effective use as anticoagulants. We examined samples containing several concentrations of argatroban or lepirudin in reconstituted standard human plasma and plasma from medical outpatients and intensive care patients. Prothrombin time (PT), activated partial thromboplastin time (aPTT), and thrombin time (TT) were determined using automated analyzers. Ecarin clotting time (ECT) was measured using a 10 IU/mL dilution of ecarin in 0.05 mol/L CaCl2. Calibration curves were approximately linear for TT and ECT in samples containing argatroban and lepirudin, respectively. Activated partial thromboplastin curves reached a plateau at DTI concentrations ≥2 µg/mL, suggesting that the aPTT may not reliably detect overdosing. Prothrombin time increased exponentially. A broad range of clotting times was seen in patient samples with all tests suggesting that individual morbidity and therapies may strongly influence test results and may lead to underestimation of DTI doses.